Modeling and Validation of Material Removal Based on Rheological Behavior Under Dynamic-Viscosity Nonlinear Coupling Effects - Tianchen Zhao; Luguang Guo; Qilong Gao; Xu Wang; Binghai Lyu; Chen Li (Micromachines)
Compliant rheological polishing advanced in facilitating the generation of smooth curved surfaces. However, the inherent energy dissipation of the medium during flow results in an uncontrollable material removal distribution. This study proposes utilizing the motion of the tool to regulate the distribution of physical fields within the computational domain, thereby controlling material removal. A film thickness model is developed based on fluid dynamics and tribology principles to examine the pressure and velocity distributions within the film. In conjunction with contact mechanics and metallography, a material removal model is formulated and then validated and refined by valid experiment, demonstrating a positive correlation between material removal rate and surface quality. Optimization experiments produced a curved surface with an Ra of 17.59 nm.